Methanotrophs: Discoveries, Environmental Relevance, and a Perspective on Current and Future Applications - Guerrero-Cruz, Simon; Vaksmaa, Annika; Horn, Marcus A.; Niemann, Helge; Pijuan, Maite; Ho, Adrian (Frontiers in Microbiology, 2021)
Methane is the final product of the anaerobic decomposition of organic matter. The conversion of organic matter to methane (methanogenesis) as a mechanism for energy conservation is exclusively attributed to the archaeal domain. Methane is oxidized by methanotrophic microorganisms using oxygen or alternative terminal electron acceptors. Aerobic methanotrophic bacteria belong to the phyla Proteobacteria and Verrucomicrobia, while anaerobic methane oxidation is also mediated by more recently discovered anaerobic methanotrophs with representatives in both the bacteria and the archaea domains. The anaerobic oxidation of methane is coupled to the reduction of nitrate, iron, manganese, sulfate, and organic electron acceptors (e.g. humic substances) as terminal electron acceptors. This review highlights the relevance of methanotrophy in natural and anthropogenically-influenced ecosystems, emphasizing the environmental conditions, distribution, function, co-existence, interactions, and the availability of electron acceptors that likely play a key role in regulating their function. A systematic overview of key aspects of ecology, physiology, metabolism, and genomics is crucial to understand the contribution of methanotrophs in the mitigation of methane efflux to the atmosphere. We give significance to the processes under microaerophilic and anaerobic conditions of both aerobic and anaerobic methane oxidizers. In the context of anthropogenically-influenced ecosystems, we emphasize the current and potential future applications of methanotrophs from two different angles, namely methane mitigation in wastewater treatment through the application of anaerobic methanotrophs, and the biotechnological applications of aerobic methanotrophs in resource recovery from methane waste streams. Finally, we identify knowledge gaps that may lead to opportunities to harness further the biotechnological benefits of methanotrophs in methane efflux mitigation and for the production of valuable bioproducts enabling a bio-based and circular economy.